From Inviting Ellipses to Radical Honesty: Judy Blume, Jason Reynolds, and the Endless Censorship of Sex. - Musgrave, Megan L. (Children's Literature, 2026)
In the face of rising censorship, young adult literature remains a vital source of comprehensive sex education. Building from a foundation established by Judy Blume's Forever... (1975), Jason Reynolds advocates for a different approach in a digital age when explicit sexual material is widely available, but models of healthy communication about sex are elusive.